THE GAPS ANALYSIS IN IMPLEMENTATION OF CLIMATE CHANGE POLICIES IN INDONESIA BASED ON ACTUAL OUTCOMES - Muh. Didik Ismu Prihandeni (INJOSEDU: International Journal of Social and Education, 2026)
This journal aims to analyse the gaps in the implementation of climate change policies based on actual results occurring in Indonesia. The research methodology used is qualitative descriptive, which will help the paper understand the phenomenon and find facts about the gaps in the implementation of climate change policies in Indonesia. Methods of data collection using document studies. The results show that the implementation of climate change policies in Indonesia has not been maximised due to various regulations, meaning Indonesia has not been able to meet its commitments to the Paris agreement.  Reasons for the lack of progress include a lack of budgetary intervention in supporting various climate change policy programmes, Indonesia's economic development that is not in accordance with its climate change commitments, and ongoing deforestation